A Combined Lidar-Polarimeter Inversion Approach for Aerosol Remote Sensing Over Ocean - Xu, Feng; Gao, Lan; Redemann, Jens; Flynn, Connor J.; Espinosa, W. Reed; da Silva, Arlindo M.; Stamnes, Snorre; Burton, Sharon P.; Liu, Xu; Ferrare, Richard; Cairns, Brian; Dubovik, Oleg (Frontiers in Remote Sensing, 2021)
An optimization algorithm is developed to retrieve the vertical profiles of aerosol concentration, refractive index and size distribution, spherical particle fraction, as well as a set of ocean surface reflection properties. The retrieval uses a combined set of lidar and polarimeter measurements. Our inversion includes using (1) a hybrid radiative transfer (RT) model that combines the computational strengths of the Markov-chain and adding-doubling approaches in modeling polarized RT in vertically inhomogeneous and homogeneous media, respectively; (2) a bio-optical model that represents the water-leaving radiance as a function of chlorophyll-a concentration for open ocean; (3) the constraints regarding the smooth variations of several aerosol properties along altitude; and (4) an optimization scheme. We tested the retrieval using 50 sets of coincident lidar and polarimetric data acquired by NASA Langley airborne HSRL-2 and GISS RSP respectively during the ORACLES field campaign. The retrieved vertical profiles of aerosol single scattering albedo (SSA) and size distribution are compared to the reference data measured by University of Hawaii’s HiGEAR instrumentation suite. At the vertical resolution of 315 m, the mean absolute difference (MAD) between retrieved and HiGEAR derived aerosol SSA is 0.028. And the MADs between retrieved and HiGEAR effective radius of aerosol size distribution are 0.012 and 0.377 micron for fine and coarse aerosols, respectively. The retrieved aerosol optical depth (AOD) above aircraft are compared to NASA Ames 4-STAR measurement. The MADs are found to be 0.010, 0.006, and 0.004 for AOD at 355, 532 and 1064 nm, respectively.